2011
DOI: 10.4069/kjwhn.2011.17.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nursing Interventions Performed by Gynecological Nursing Unit Nurses Using the Nursing Interventions Classification

Abstract: at one hospital and analyzed by using frequencies in the Microsoft Excel 2010 program. Results: Of a total of 82 NIC, domains of the nursing interventions showed higher percentages for physiological: basic (36.3%) and physiological: complex (34.5%). The classes of nursing interventions showed higher percentage for health system mediation (12.1%), perioperative care (10.0%), and drug management (8.6%). The most frequently used top interventions were Discharge Planning. The thirty least used interventions was en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Acute pain (00132) was documented for all patients including those in the internal medicine and surgery nursing unit (Ko & So, ), surgery nursing unit (Lee & Choi, ), and recovery room (Cho & Kim, ), as well as those who received chemotherapy (Song et al., ), those who underwent abdominal surgery (Yoo & Chi, ), and upon comparison of NNN linkages between nursing units (Kim, ). Risk for infection (00004) was documented for patients in the obstetrics nursing unit (Hong, Lee, & Kim, ), general surgery nursing unit (Lee & Choi, ), as well those who underwent abdominal surgery (Yoo & Chi, ). Nausea (00134) was documented for patients in the internal medicine and surgery nursing unit (Ko & So, ), general surgery nursing unit (Lee & Choi, ), and recovery room (Cho & Kim, ), as well as upon comparison of NNN linkage between nursing units (Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute pain (00132) was documented for all patients including those in the internal medicine and surgery nursing unit (Ko & So, ), surgery nursing unit (Lee & Choi, ), and recovery room (Cho & Kim, ), as well as those who received chemotherapy (Song et al., ), those who underwent abdominal surgery (Yoo & Chi, ), and upon comparison of NNN linkages between nursing units (Kim, ). Risk for infection (00004) was documented for patients in the obstetrics nursing unit (Hong, Lee, & Kim, ), general surgery nursing unit (Lee & Choi, ), as well those who underwent abdominal surgery (Yoo & Chi, ). Nausea (00134) was documented for patients in the internal medicine and surgery nursing unit (Ko & So, ), general surgery nursing unit (Lee & Choi, ), and recovery room (Cho & Kim, ), as well as upon comparison of NNN linkage between nursing units (Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…간호기록에 관한 최근의 연구들을 살펴보면, 국내 전 자간호기록 개발 및 사용 관련 연구 (Cho et al, 2013;Cho et al, 2015a;Cho et al, 2015b;Park, Kim, & Hong, 2013), 전자의무기록에 대한 만족도 관련 연 구 (Ha, 2017), 간호기록 분석 (Im & Yi, 2012;Hong, Lee, & Kim, 2011) 등에 대한 내용들이 대부분이었 다. 간호기록 작성방법에 대한 지식과 관련된 연구로는 지식측정도구 개발 연구 (Kim & Park, 2007), 법적 관 점의 간호기록 작성방법 교육 관련 연구 (Kim, 2013; (Martilla & James, 1977).…”
Section: 간호기록은 건강관리전달체계의 변화와 함께 간호사의unclassified
“…To date, the NIC has been implemented in nursing information systems at national, as well as international levels in order to describe and capture the interventions performed by nurses (Haugsdal & Scherb, ). Recent studies using the NIC in Korea were conducted in diverse nursing practice care settings (Oh et al ., ; Yong et al ., ; Kwon & Park, ; Lee & Park, ; Oh & Park, ; Choi et al ., ; Park & Jung, ; Cho & Kim, ; Hong et al ., ). All of these studies reported that the NIC is applicable for use in describing nursing practice in Korea.…”
Section: Introductionmentioning
confidence: 97%